Faktor yang Berhubungan dengan Pemberian Asi Ekslusif di Wilayah Kerja Puskesmas Tampo Kecamatan Napabalano Kabupaten Muna Tahun 2023 - Tiara Cyndi Pradewi Harlin; Harleli Harleli; Syefira Salsabila (Universitas Pahlawan Tuanku Tambusai, 2023)
Breast milk is the main food for babies. Breast milk is the main source of life for babies until the age of 6 months. For 6 months, babies are expected to drink only breast milk without any other additions or often called exclusive breastfeeding. This study aims to determine the factors associated with exclusive breastfeeding behavior in the working area of tampo puskesmas, napabalano sub-district, muna district in 2023. This type of research is quantitative research and analytic survey design with a cross sectional approach. This study used a total sampling technique with a sample size of 75 respondents. Data analysis using univariate and bivariate analysis using the chi square test. The results of statistical tests using the chi-square test show that, there is a relationship between maternal knowledge and exclusive breastfeeding with a value (p = <0.05), there is a relationship between formula milk promotion and exclusive breastfeeding (p = <0.05), The conclusion in this study is that the factors associated with exclusive breastfeeding in the working area of tampo health center, napabalano sub-district, muna district are knowledge,andformula milk promotion It is recommended to the health center to add counseling sessions in every posyandu activity so that the benefits of breast milk can be conveyed to breastfeeding mothers so that mothers are more motivated to do exclusive breastfeeding to their babies, to mothers During pregnancy, mothers need to actively consult midwives who conduct pregnancy checks to obtain information related to breastfeeding and get motivation from health workers to continue to do exclusive breastfeeding to their babies.